2010
DOI: 10.1093/infdis/jiq057
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus RNA Not Detected in Urine of 40 People Tested 6 Years After Acute West Nile Virus Disease

Abstract: West Nile virus (WNV) causes an acute infection that is usually cleared by an effective immune response after several days of viremia. However, a recent study detected WNV RNA in the urine of 5 of 25 persons (20%) tested several years after their initial acute WNV disease. We evaluated an established cohort of 40 persons >6 years after initial infection with WNV. Urine collected from all participants tested negative for WNV RNA by reverse-transcription polymerase chain reaction and transcription-mediated ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…This has been suggested by viral RNA detection in human whole blood out to 90 days postinfection, nucleic acids in tissues in a mouse model out to 6 months, and RNA detection in urine from previously infected humans out to 6 years (16)(17)(18). However, others have not been able to verify the latter finding (19).…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested by viral RNA detection in human whole blood out to 90 days postinfection, nucleic acids in tissues in a mouse model out to 6 months, and RNA detection in urine from previously infected humans out to 6 years (16)(17)(18). However, others have not been able to verify the latter finding (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in some cases convalescent patients may have persistent or chronic infection detected through PCR of the urine, which suggested ongoing viral replication in renal tissue (141,143). Although persistence of WNV has also been noted in several animal models (156,199,213), it has not been uniformly evident in assays of urine (66).…”
Section: Mammalian Infection Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…In one study, WNV RNA was detected in a subset of patients with persistent symptoms 1-7 years post WNV infection [90]. However, in a separate study of WNV patients >6 years post infection, WNV RNA was not detected in the urine [91, 92]. However, a recent study showed that high levels of WNV RNA could be amplified in urine during acute infection and up to 30 days after presentation [93].…”
Section: Controversies In Virus Persistence and Immune Responsesmentioning
confidence: 99%